Helicobacter pylori Antral Density More Valuable than Corporal Density in Chronic Gastritis Patients - Bernadetta Jonan; Willy Sandhika; Ummi Maimunah; Muhammad Miftahussurur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: Helicobacter pylori has the capacity to colonize in stomach. In countries with a high prevalence of H. pylori, biopsy specimens must be obtained from corpus and antrum to elevate the accuracy. However, in a country with low prevalence of H. pylori such as Indonesia, the sensitivity of antrum specimen only is still questionable. We compared the density of H. pylori in the antrum and corpus of Indonesian gastric biopsy.Method: We conducted a prospective, cross-sectional, and observational study in thirty-two samples of corpus and antrum biopsy tissues from Pathology Anatomy Laboratory. The samples were stained by Modified Giemsa or Diff Quik. Updated Sydney System is utilized to classify the density of H. pylori.Results: Among 32 biopsy specimens from corpus and antrum, it has been statistically proven that H. pylori density in antrum and in corpus has a significant difference (65.5% vs. 15.6%, p 0.001). The density of H. pylori in antrum is mild predominant (43.8%), while the density in corpus is normal predominant (87.5%). Thus, the antral H. pylori infection was the predominant site. In 53.12% case, H. pylori was found in antrum but was not found in the corpus. In 6.24% case, H. pylori was found in both sites, but the density was higher in antrum. Importantly, no case with H. pylori infection in corpus only was found.Conclusion:  H. pylori density in antrum is higher than in corpus. Only a small advantage to use additional biopsy from corpus to detect H. pylori in Indonesia.